Healthy Stadia 2018
DOI: 10.4324/9781315147079-12
|View full text |Cite
|
Sign up to set email alerts
|

‘It brings the lads together’: a critical exploration of older men’s experiences of a weight management programme delivered through a Healthy Stadia project

Abstract: It brings the lads together': A critical exploration of older men's experiences of a weight management programme delivered through a Healthy Stadia project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…These values facilitated participation and positive involvement, social interactions, caring relationships, and a supportive atmosphere. This enhanced the relevance and meaningfulness of their participation in sport [47]. A qualitative study by Mynard et al (2009) supports the notion of inclusive competition identified as a "spirit of inclusion."…”
Section: Competitive Versus Non-competitive Structurementioning
confidence: 65%
See 4 more Smart Citations
“…These values facilitated participation and positive involvement, social interactions, caring relationships, and a supportive atmosphere. This enhanced the relevance and meaningfulness of their participation in sport [47]. A qualitative study by Mynard et al (2009) supports the notion of inclusive competition identified as a "spirit of inclusion."…”
Section: Competitive Versus Non-competitive Structurementioning
confidence: 65%
“…These values facilitated participation and positive involvement, social interactions, caring relationships, and a supportive atmosphere. This enhanced the relevance and meaningfulness of their participation in sport [47]. A qualitative study by Mynard et al (2009) supports the notion of inclusive competition identified as a “spirit of inclusion.” They argued that a spirit of inclusion in Australian rules football fostered team building and a collective culture of friendship, cooperation, and support, making the participants’ team involvement meaningful [51].…”
Section: Content Theme Analysismentioning
confidence: 99%
See 3 more Smart Citations